Immigration and Adult Children's Care for Elderly Parents: Evidence from Western Europe - Andrea Berlanda; Elisabetta Lodigiani; Lorenzo Rocco (Institute of Labor Economics (IZA), 2025)
In this paper, we use the Survey of Health, Ageing, and Retirement in Europe (SHARE), complemented with register data on the share of the foreign population in the European regions, to examine the effects of migration on the level of informal care provided by children to their senior parents. Our main results show that migration decreases informal care among daughters with a university degree, while it increases the provision of informal care among daughters with low-to-medium levels of education. Viceversa, migration has practically no effect on sons' care provision who remain little involved in care activities. These results depend on the combination of two supply effects. First, migration increases the supply of domestic and personal services, making formal care more affordable and available. Second, as immigrants compete with low-to-medium-educated native workers, while improve the labor market opportunities of the better educated, the supply of informal care can increase among the less educated daughters and decrease among the more educated.
Keywords: F22; J14; J22; 330; immigration; home production; caregiving; Europe